Статті Симона Петлюри на сторінках журналу “Тризуб” під псевдонімами - Гриненко, О. (Науковi записки. Збiрник праць молодих вчених та аспiрантiв, 2010)
В журналі “Тризуб” за 1925–1926 роки були опубліковані статті С. Петлюри під псевдонімами, в яких гостро критикується влада більшовиків в Україні, висвітлюються національні питання, піднімаються проблеми українізації, приділяється увага українській пресі на еміграції. В журнале “Тризуб” за 1925–1926 года были опубликованы статьи С. Петлюри под псевдонимами, в которых остро критикуется власть большевиков, освещаются национальные вопросы, поднимаются проблемы украинизации, уделяется внимание украинской печати в эмиграции. In 1925 and 1926 in the magazine “Tryzub” S. Petlura published his articles under the pseudonyms. In these articles the power of Soviet authorities in Ukraine was strongly criticized. The national question was highlighted as well. The problem of implementing the Ukrainian language in all spheres of social life was a point at issue. Also the great attention was dedicated to the Ukrainian Press in immigration.